Application of a Multiplex Polymerase Chain Reaction Test for Diagnosing Bacterial Enteritis in Children in a Real-Life Clinical Setting - Lee, Hyun-Woo; Han, Seung-Beom; Rhim, Jung-Woo (Children (Basel), 2021)
This study aimed to determine the subjects for bacterial multiplex polymerase chain reaction (mPCR) testing and to interpret the mPCR test results based on patients’ clinical symptoms and diagnoses. The medical records of 710 pediatric patients who underwent a bacterial mPCR test were retrospectively reviewed. Clinical characteristics and mPCR test results were compared between patients with positive (n = 199) and negative mPCR test results (n = 511) and between patients with invasive pathogens (n = 95) and toxigenic pathogens (n = 70). Positive mPCR test results were significantly associated with older age (p < 0.001), diagnosis of acute gastroenteritis (p = 0.021), presence of hematochezia (p < 0.001), and absence of cough (p = 0.004). The diagnosis of acute gastroenteritis (p = 0.003), presence of fever (p = 0.027) and diarrhea (p = 0.043), and higher C-reactive protein levels (p = 0.025) were significantly associated with the identification of invasive pathogens in patients with positive mPCR test results. Thus, selective bacterial mPCR testing should be performed based on the patients’ clinical symptoms and diagnoses, and the results should be interpreted in consideration with identified pathogens.